The Expression of KLF11 (TIEG2), a Monoamine Oxidase B Transcriptional Activator in the Prefrontal Cortex of Human Alcohol Dependence. (5th August 2013) - Udemgba, Chinelo; Johnson, Shakevia; Stockmeier, Craig A.; Luo, Jia; Albert, Paul R.; Wang, Junming; May, Warren L.; Rajkowska, Grazyna; Harris, Sharonda; Sittman, Donald B.; Ou, Xiao‐Ming
<x xml:space="preserve">Abstract</x> Background The biochemical pathways underlying alcohol abuse and dependence are not well understood, although brain cell loss and neurotoxicity have been reported in subjects with alcohol dependence. Monoamine oxidase B (MAO B; an enzyme that catabolizes neurotransmitters such as dopamine) is consistently increased in this psychiatric illness. MAO B has been implicated in the pathogenesis of alcohol dependence and alcohol‐induced brain neurotoxicity. Recently, the cell growth inhibitor protein, Kruppel‐like factor 11 (KLF11), has been reported to be an MAO transcriptional activator. KLF11 is also known as TIEG2 (transforming growth factor‐beta‐inducible early gene 2) and mediates apoptotic cell death. This study investigates the protein expression of KLF11 and its relationship with MAO B using human postmortem prefrontal cortex from subjects with alcohol dependence. Methods Twelve subjects with alcohol dependence and the respective psychiatrically normal control subjects were investigated. Expression of KLF11 and MAO B proteins in the prefrontal cortex was measured by Western blot analysis. Correlation studies involving KLF11 and MAO B protein expression were performed. Localization of KLF11 in the human prefrontal cortex was also determined by immunohistochemistry. Results Levels of KLF11 protein were significantly increased by 44% (p < 0.03) in the postmortem prefrontal cortex of subjects with alcohol dependence as compared to age‐ and gender‐matched, psychiatrically normal control subjects. Furthermore, KLF11 levels were significantly and positively correlated with both the increased MAO B protein levels and blood alcohol content in alcohol‐dependent subjects. In addition, KLF11 protein expression was visualized in both neuronal and glial cells. Conclusions This novel study shows the important role of KLF11, an MAO transcriptional activator, in human alcohol dependence. It further supports that the KLF11‐MAO B cell death cascade may contribute to chronic alcohol‐induced brain damage. This argues a case for KLF11‐MAO B inhibition as a novel therapeutic strategy that may impact this highly prevalent illness.